Shoreline change detection and coastal erosion monitoring using digital processing of a time series of high spatial resolution remote sensing data - Vassilakis, E; Tsokos, Α.; Kotsi, Ε. (14th Intern. Conf. of the Geological Society of Greece, 2016)
The long term change of the shoreline is a phenomenon, which is factored in the design of construction projects along the coastal zone. This study presents a meth-odology that aims to quantify the shoreline displacement rate. The described meth-odology involves the interpretation of different remote sensing data types, which make up a quite dense time series of representations for the coastline spanning from 1987 to 2012. The representation of the shoreline is based on geometrically corrected (ortho-rectified), historical, analogue, panchromatic, high resolution aerial photos of the area (1987, 1996) and latest generation, digital, multispectral, high resolution satellite images (2000, 2008, 2012). In all cases the images were digitally processed and optically optimized in order to produce a highly accurate representation of the shoreline in each time period. All the data were imported in a Geographic Information System platform, where they were subjected to comparison and geo-statistical analysis. A large number of sections perpendicular to the coast (every 100 meters) was drawn and the relative motion of the coastline was calcu-lated for each of them. The average rate of the calculated erosion is in the order of 24mm/year whilst extreme rates of 1m/year were also observed in specific posi-tions.